The Impact of Nutritional Counseling Using Flyers on Knowledge of Chronic Energy Deficiency (CED) Among Pregnant Women - Desidarius Bela Dhesa; Asran Asran; Jenny Qlifianti Demmalewa (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Chronic energy deficiency (CED) is one of the nutritional problems of pregnant women that can be prevented through counseling. The prevalence of CED at Waara Community Health Center increased from 2022 (20.9%), in 2023 (29.8%), and in 2024 (32.2%). The purpose of this study was to determine the effect of nutritional counseling using flyers on pregnant women’s knowledge of CED. This research is a pre-experimental study with a one-group pre-test and post-test design. This study was conducted in the working area of the Waara Community Health Center in Muna Regency from Juny 6 to November 10, 2025. The sample comprised 27 pregnant women in the working area of the Waara Community Health Center in 2025, during the October to November period, selected through total sampling. Data were collected using a questionnaire to measure knowledge about CED and tested using a paired t-test. The results of the study on 27 samples, the average score of knowledge of pregnant women increased from 7.00 to 10.00. The results of the paired t-test obtained a p < 0.001. The conclusion is that nutritional counseling using flyers resulted in a significant increase in knowledge about CED among pregnant women in the Waara Community Health Center, Muna Regency Keywords: Counseling, Flyer, Knowledge, Nutrition, Pregnant women